How to measure the impact of premenstrual symptoms? Development and validation of the German PMS-Impact Questionnaire - Kues, Johanna N.; Janda, Carolyn; Kleinstäuber, Maria; Weise, Cornelia (Women & Health, 2016)
With 75% of women of reproductive age affected, premenstrual symptoms are very common, ranging from emotional and cognitive to physical symptoms. Premenstrual Syndrome and Premenstrual Dysphoric Disorder can lead to substantial functional interference and psychological distress comparable to that of dysthymic disorders. The assessment of this impact is required as a part of the diagnostic procedure in the DSM-5. In the absence of a specific measure, the authors developed the PMS-Impact Questionnaire. A sample of 101 women reporting severe premenstrual complaints was assessed with the twenty-two items in the questionnaire during their premenstrual phase in an ongoing intervention study at the Philipps-University Marburg from August 2013 until January 2015. An exploratory factor analysis revealed a two-factor solution (labeled Psychological Impact and Functional Impact) with 18 items. A Cronbach’s alpha of 0.90 for Psychological Impact and of 0.90 for Functional Impact indicated good reliability. Convergent construct validity was demonstrated by moderate to high correlations with the Pain Disability Index. Low correlations with the Big Five Inventory-10 indicated good divergent validity. The PMS-Impact Questionnaire was found to be a valid, reliable, and an economic measure to assess the impact of premenstrual symptoms. In future research, cross validations and confirmatory factor analyses should be conducted.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Disability; distress; interference; menstruation; Premenstrual Dysphoric Disorder (PMDD); Premenstrual Syndrome (PMS); psychometric properties